“The Impact Of Digital Wallets Threats And Safety Measures On The Level Of Usage” – A Study With Reference To Chennai (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Digital wallet refers to an electronic system that enables a person to make purchases on a commodity or commodity class basis. It is a device that safely stores the payment details and password of consumers for the variety of payment methods and websites. The wallet may be Computer, Web, Smartphone or hardware wallets. Any payment by online format is subject to the limitations and threats of data security, which contribute to an increase in safety awareness of the use of information. Electronic wallets are used in the banking, investment, insurance, retail, educational, travel, entertainment and utility industries. The objective of this research study is to determine possible risks and safety measures for safer management of e-wallets and increased accessibility. An empiric research was performed by surveying 80 respondents and evaluating the data obtained by applying statistical methods such as one direction ANOVA, Matched t-test by using SPSS and Confirmatory multivariate statistical using Amos software. A simple structural equation modelling is often used to define a relationship between dependent and independent variables.